Quality control requirements for the correct annotation of lipidomics data - Koefeler, Harald C; Eichmann, Thomas O; Ahrends, Robert; Bowden, John A; Danne-Rasche, Niklas; Dennis, Edward A; Fedorova, Maria; Griffiths, William J; Han, Xianlin; Hartler, Juergen; Holčapek, Michal; Jirásko, Robert; et al. (Nature Publishing Group, 2021)
Automated lipid species annotation based on fragment ion mass spectra faces three major challenges; isobaric or isomeric lipid species from different classes often yield similar fragments and cannot be unambigiously matched; the abundance of lipid fragments strongly depends on the experimental conditions which compromises their similarity to reference spectra; fragmentation of co-isolated precursors often originating from different classes yields highly convoluted spectra.
Požadavky na kontrolu kvality pro správnou anotaci lipidomických údajů
Keywords: identification; lipidomics data; identifikace; lipidomické údaje